2024
DOI: 10.1162/imag_a_00075
|View full text |Cite
|
Sign up to set email alerts
|

A database of the healthy human spinal cord morphometry in the PAM50 template space

Jan Valošek,
Sandrine Bédard,
Miloš Keřkovský
et al.

Abstract: Measures of spinal cord morphometry computed from magnetic resonance images serve as relevant prognostic biomarkers for a range of spinal cord pathologies, including traumatic and non-traumatic spinal cord injury and neurodegenerative diseases. However, interpreting these imaging biomarkers is difficult due to considerable intra- and inter-subject variability. Yet, there is no clear consensus on a normalization method that would help reduce this variability and more insights into the distribution of these morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…However, the spine-generic database identifies an additional 61 subjects with mild degenerative compression and 2 subjects with severe degenerative compression and radiological myelopathy. 49 Analysis power decreased, but minimal nuances were detected in correlation coefficients when tested separately on subjects without or with degenerative cervical SC compression (see Supplementary Slides ). Thus, we conclude that SC compression had a minimal impact on the current study outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…However, the spine-generic database identifies an additional 61 subjects with mild degenerative compression and 2 subjects with severe degenerative compression and radiological myelopathy. 49 Analysis power decreased, but minimal nuances were detected in correlation coefficients when tested separately on subjects without or with degenerative cervical SC compression (see Supplementary Slides ). Thus, we conclude that SC compression had a minimal impact on the current study outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the prevalence of spinal cord compression increases with age 11,38,42 . Further work will include extending the normative database 11 to a wider age range.…”
Section: Impact Of Across-subject Normalizationmentioning
confidence: 93%
“…Therefore, we implemented the normalization approach for several morphometric measures provided by SCT's sct_process_segmentation. Those metrics are: 1) AP diameter, 2) RL diameter, 3) CSA, 4) eccentricity, and 5) solidity 11 . Note that the original MSCC normalizes only the AP diameter 13 (see Figure 1B).…”
Section: Morphometric Measures To Characterize Spinal Compressionmentioning
confidence: 99%
See 2 more Smart Citations